Wywózki Polaków do ZSRR w latach 1944-1945. Próba interpretacji danych liczbowych – artykuł dyskusyjny - Skrzypek, Andrzej (Acta Universitatis Lodziensis. Folia Historica, 2001)
The study’s nodal problem is assignation of numeber of the Poles (Polish citizens) deported from Poland to the USSR (precisely from territories West to the Curzon’s line) between July 1944 and May 1945. The requested number docs not contain persons removed from border lands. The author quotes „legal” base of that action - the instructions of Soviet authorities, that specified categories of deported persons and separated three phases of transportations. Afterwords it gaves number of arrested people, principles of deportations’ organization and tries to identify larger transports. Analizing different reports, the article identifies camps, where the Poles were placed and verifies their number. The author estimates 51 00 (without persons that died during transportations) people were deported and 10 700 arrested, but not deported. Not more that half or them was connected with the independence conspiracy. The last part of the article compares the number of deported persons with the number of released ones and that comparison holds out the test. There were also three phases of release. That process finished in 1948. About 9000 of the deported persons did not come back to Poland. Thex partially died and partially came back in 1956.